Tourism and climate change : - Scott, Daniel (Routledge, 2012)
Tourism and Climate Change: Impacts, Adaptation and Mitigation is the first book to provide a comprehensive overview of the theory and practice of climate change and tourism at the tourist, enterprise, destination and global scales. Major themes include the implications of climate change and climate policy for tourism sectors and destinations around the world, tourist perceptions of climate change impacts, tourism’s global contribution to climate change, adaptation and mitigation responses by all major tourism stakeholders, and the integral links between climate change and sustainable tourism. It combines a thorough scientific assessment of the climate-tourism interrelationships with discussion of emerging mitigation and adaptation practice, showcasing international examples throughout the tourism sector as well as actions by other sectors that will have important implications for tourism.